Low-frequency electromagnetic fields combined with tissue engineering techniques accelerate intervertebral fusion - Weigang Li; Chunwei Huang; Tian Ma; Jiachen Wang; Wenbin Liu; Jiyuan Yan; Gaohong Sheng; Ruizhuo Zhang; Hua Wu; Chaoxu Liu (Stem Cell Research & Therapy, 2021)
Abstract Background Intervertebral fusion is the most common surgery to treat lumbar degenerative disease (LDD). And the graft material used in the operation is derived from the iliac crest to promote fusion. However, autografts possess the fatal disadvantage of lack of source. Therefore, economical and practical bone substitutes are urgently needed to be developed. Sinusoidal electromagnetic fields (EMF) combined with tissue engineering techniques may be an appropriate way to promote intervertebral fusion. Methods In this research, porous scaffolds made of polycaprolactone (PCL) and nano-hydroxyapatite (nHA) were used as cell carriers. Then, the scaffolds loaded with bone marrow mesenchymal stem cells (BMSCs) were treated with sinusoidal electromagnetic field and the osteogenic capability of BMSCs was tested later. In addition, an intervertebral disc of the tail vertebra of the rat was removed to construct a spinal intervertebral fusion model with a cell-scaffold implanted. The intervertebral fusion was observed and analyzed by X-ray, micro-CT, and histological methods. Results BMSCs stimulated by EMF possess splendid osteogenic capability under an osteogenic medium (OM) in vitro. And the conditioned medium of BMSCs treated with EMF can further promote osteogenic differentiation of the primitive BMSCs. Mechanistically, EMF regulates BMSCs via BMP/Smad and mitogen-activated protein kinase (MAPK)-associated p38 signaling pathways. In vivo experiments revealed that the scaffold loaded with BMSCs stimulated by EMF accelerated intervertebral fusion successfully. Conclusion In summary, EMF accelerated intervertebral fusion by improving the osteogenic capacity of BMSCs seeded on scaffolds and might boost the paracrine function of BMSCs to promote osteogenic differentiation of the homing BMSCs at the injured site. EMF combined with tissue engineering techniques may become a new clinical treatment for LDD.